2004
DOI: 10.1179/026708304225016743
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of precipitates, in particular cruciform and cuboid particles, during simulated direct charging of thin slab cast vanadium microalloyed steels

Abstract: A study has been undertaken of four vanadium based steels which have been processed by a simulated direct charging route using processing parameters typical of thin slab casting, where the cast product has a thickness of 50 to 80mm ( in this study 50 mm) and is fed directly to a furnace to equalise the microstructure prior to rolling. In the direct charging process, cooling rates are faster, equalisation times shorter and the amount of deformation introduced during rolling less than in conventional practice. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 17 publications
7
42
1
Order By: Relevance
“…208 The vanadium steels he considered were all studied by Li et al 56,176,177 It is of interest to note that no observations of interphase precipitation were recorded in this work. In V-N steel (0?10V-0?022N, wt-%), following a low equalisation treatment at 1050uC, cuboidal precipitates were observed along austenite grain boundaries (Fig.…”
Section: Thin Slab Cast and Direct Rolling Processed Steelsmentioning
confidence: 97%
See 2 more Smart Citations
“…208 The vanadium steels he considered were all studied by Li et al 56,176,177 It is of interest to note that no observations of interphase precipitation were recorded in this work. In V-N steel (0?10V-0?022N, wt-%), following a low equalisation treatment at 1050uC, cuboidal precipitates were observed along austenite grain boundaries (Fig.…”
Section: Thin Slab Cast and Direct Rolling Processed Steelsmentioning
confidence: 97%
“…In fact, the work showed that sub-15 nm particles were nitrogen rich carbonitrides which do not appear to coarsen during the final stages of processing. 154,[175][176][177][178] The carbon extraction replica technique has the advantage of giving good contrast for extracted particles, low background for analysis using PEELS and EDX spectroscopy, and no perturbation of the optical properties of the objective lens from the ferromagnetic material in a typical foil specimen. However, there is some uncertainty about the extraction efficiency for the smallest particles, as very few were found with sizes ,4 nm.…”
Section: Methods For Analysis Chemical Composition Of Vanadium Precipmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium additions to microalloyed steels increased the toughness of the steel because the formation of nanoscale, cruciform precipitates removed nitrogen, vanadium and niobium that ordinarily would have precipitated in ferrite as dispersion hardening particles and kept the material toughness low (15). Nanosized (15 nm) dispersoids of Al 7 Cr played a major role in pinning subboundaries thus allowing superplasticity to occur in an Al-Mg-Mn alloy (24) while boron additions to Type 347 stainless steels caused enhanced the precipitation of carbonitrides and nanosized borides which increased the creep strength (18) by inhibiting grain boundary sliding.…”
Section: Traditional Metallurgy Nanoparticles and The Relatively Recmentioning
confidence: 99%
“…A glance at the recent materials engineering and science literature demonstrates the wide spread industrial application of nanotechnologies by the traditional metallurgists. By controlling the formation of nanoparticles in various alloys, researchers have increased material toughness (15,16), strength (16,17) and creep (18) and fatigue (16) resistance, improved age hardening kinetics (17,19), increased the quality of hot-isostatically pressed super alloys (20), improved the mechanical properties of cast alloys (21), developed superior shape memory characteristics (22), increased the work hardening rates (23) and induced superplasticity (24).…”
Section: Traditional Metallurgy Nanoparticles and The Relatively Recmentioning
confidence: 99%